Analysis of the causes of failure in 5Cr-1Mo pipes mounted in a preheating furnace - Adelina Borruto; Giovanni Narducci; Pietro Pietrosanti (Fracture and Structural Integrity)
The oxidation resistance of iron-based alloys depends on the formation of thin protective films consisting of reaction products between the alloys and the ambient atmosphere. The high corrosion resistance of Fe-Cr-Mo alloys has been attributed to the rapid formation of a uniform, highly protective passive film. The pipes hardness and resistance to various forms of corrosion are determined by the composition of the oxide layer that plays an important role in determining the lifetime of the pipes themselves. The thermal stability of the oxide layer is influenced by its composition and thickness as well as by the bond to the underlying metal.Determining factors for the high temperature corrosion are generally: temperature, metallurgy, TAN (chloridric and naphthenic acid), local flow conditions, sulphur compounds.